How Patient Complexity and Surgical Approach Influence Episode-Based Payment Models for Colectomy - Sheetz, Kyle H. (Dis Colon Rectum, 2019)
BACKGROUND: Bundled payment programs broaden hospitals’ responsibility for spending to entire episodes of care. After demonstration programs in cardiac surgery and joint replacement, these payment reforms could soon extend to major operations like colectomy under Medicare’s Bundled Payments for Care Improvement-Advanced Program. OBJECTIVE: To evaluate how specific policies and surgical practice patterns would influence hospital reimbursement in a bundled payment program for colectomy. DESIGN: This was a population-based study. SETTINGS: We used national data from the 100% Medicare Provider Analysis and Review files for the years 2010 to 2014. PATIENTS: We identified patients undergoing colon resections using Diagnosis Related Group codes and International Classification of Disease, Ninth Revision, Clinical Modification codes. MAIN OUTCOME MEASURES: We simulated per case reconciliation payments as the difference between actual price-standardized 90-day episode payments and estimated regional spending benchmarks among fee-for-service Medicare beneficiaries undergoing colectomy (2010-2014).We projected per-patient and overall hospital-level reconciliation payments and the proportion of hospitals that would achieve shared shavings under bundled payment conditions. We also assessed how variation in the use of laparoscopy could influence shared savings, using instrumental variable methods to account for selection bias between laparoscopic and open procedures. RESULTS: Under simulated bundled payment conditions, 51.8% of hospitals would achieve shared savings, but the average case would incur a reconciliation penalty of −$234 (95% CI −$245 to −$223). Risk-adjustment would increase the proportion of hospitals with shared savings to 54.3% (per case payment +$237, 95% CI $96 to $379). Hospitals performing a greater proportion of cases laparoscopically would achieve higher per case reconciliation payments. For example, per case reconciliation penalties would be −$472 (95% CI −$506 to −$438) for hospitals that performed 10% of their procedures laparoscopically, whereas those that performed 70% laparoscopically would receive payments of +$294 (95% CI $262 to $326). LIMITATIONS: Alternative payment models for colectomy have not yet been introduced. CONCLUSIONS: Surgical leaders must be prepared with strategies for optimizing episode efficiency. Inclusion of risk-adjustment in bundled payment calculations and expanding utilization of laparoscopic surgery may represent approaches to achieve shared-savings and improve surgeon engagement in alternative payment models for surgical care. See Video Abstract at http://links.lww.com/DCR/A928.